Medical management of patients on clozapine: A guide for internists. Issue 8 (23rd March 2015) - Lundblad, Wynne; Azzam, Pierre N.; Gopalan, Priya; Ross, Clinton A.; PharmD
<x xml:space="preserve">Abstract</x> Clozapine was approved by the US Food and Drug Administration in 1989 for the management of treatment‐resistant schizophrenia, and has since proven to reduce symptom burden and suicide risk, increase quality of life, and reduce substance use in individuals with psychotic disorders. Nevertheless, clozapine's psychiatric benefits have been matched by its adverse effect profile. Because they are likely to encounter medical complications of clozapine during admissions or consultations for other services, hospitalists are compelled to maintain an appreciation for these iatrogenic conditions. The authors outline common (eg, constipation, sialorrhea, weight gain) and serious (eg, agranulocytosis, seizures, myocarditis) medical complications of clozapine treatment, with internist‐targeted recommendations for management, including indications for clozapine discontinuation. Journal of Hospital Medicine 2015;10:537–543. © 2015 Society of Hospital Medicine